Analogous behavior of pseudo-slug and churn flows in high viscosity liquid system and upward inclined pipes. (June 2018) - Soedarmo, Auzan; Soto-Cortes, Gabriel; Pereyra, Eduardo; Karami, Hamidreza; Sarica, Cem
Highlights: Characterizations of high viscosity oil/ air churn and pseudo-slug flows are presented. Analogous behaviors between pseudo-slug and churn flows are explained. Approaches to model transition between slug and pseudo-slug flows are presented. Abstract: Pseudo-slug (PS) and churn (CH) flows are among the least understood flow patterns for gas-liquid flow in pipes, despite their importance in many engineering applications. Owing to visual differences, they are commonly perceived as different flow patterns. This study presents characterizations of these flow patterns, which suggests their analogous behavior, thus enabling possibility of unified modeling between them. The experiments were conducted using an air-oil (0.213 Pa.s liquid viscosity) system with a 0.0508-m ID, 21.7-m long, upward inclined polycarbonate test section under atmospheric pressure. Flow patterns were identified using the dimensionless voltage time-trace readings of two-wire capacitance probes, supplemented by high-speed camera observations. The capacitance probes were used for slug/ pseudo-slug/ churn flow characterizations. Additionally, capillary-seal differential pressure transmitters for pressure drop measurement and quick-closing-valves section for liquid holdup measurement were used. Experimental results demonstrate that despite their visual differences, PS and CH share several common characteristics. First, both PS and CH exist between slug (SL) and segregated flows (annular or stratified) as superficial gas velocity ( v SG ) changes in the flow pattern map. Second, non-monotonic relationships between translational and mixture velocities are observed for both flow patterns in contrast to linear behavior for conventional SL flow. Third, both flow patterns exhibit similar signature of capacitance probes time-trace data and its distribution histogram. Fourth, they show similar values of drift-flux flow distribution coefficient ( C0 ). And fifth, a consistent bias tendency is observed when conventional SL flow models are used to predict the pressure gradient of both flow patterns. The visual difference between PS and CH may be attributed to higher frequency, wavier film interface, and more uniform pipe wetting exhibited by CH compared to PS flow due to inclination angle effects. Several SL to CH transition models are modified/ extended to predict SL to PS transition. The combination of Taylor bubble flooding and a unified slug flow model is found to predict the SL to PS transition accurately within the experimental range, further supporting the analogy between PS and CH.